Dominant Factors Influencing Anemia Prevention Behavior among Young Women in Depok City in 2023. - Nurmadinisia, Rahmi (Jurnal Kesehatan Masyarakat, 2024)
Anemia is still a global public health problem due to the high prevalence of anemia among adolescent girls and women of childbearing age. Anemia is also one of the main contributors to DALYs (disability-adjusted life years) in adolescents, so the problem of adolescent anemia needs to be addressed seriously because it impacts the quality of human resources. There are many factors that influence anemia prevention behavior in adolescent girls. Currently, the prevalence of anemia in Depok City is 16.6%, although there has been a decrease compared to the previous year 13. However, anemia is still in the top 20 causes of hospitalization in Depok City. Apart from that, anemia in young women is a risk of having stunted babies later in life, which is one of the main factors for SDG's in Indonesia. The aim of this research is to determine the dominant factors that influence anemia prevention behavior among adolescent girls in Depok City. The research method used is a quantitative method with a cross-sectional design. The total sample in this study was 221 respondents using disproportionate random sampling technique. Data analysis was carried out through multivariate analysis using multiple logistic regression tests. The results of the study showed that 45% of teenagers had behaved to prevent anemia. The variables attitude, mother support, and access to information have a significant relationship with anemia prevention behavior (p value 0.05. Access to information is the dominant factor influencing anemia prevention behavior. Applications that are upgraded and up to date are needed for the substance of the information provided so that There has been an increase in anemia prevention behavior among young women in Depok City.